Modeling Goal-Directed Choice Quality: A University Context - Simamora, Bilson (International Review of Management and Marketing, 2020)
Can we detect future student loyalty at the moment of university choice? Based on the expectancy-value belief theory, the author develops the model of goal-directed student decision quality to answer that question. The premise is that decision quality determines loyalty intention, and the achievement goals impact both. Therefore, the objectives of this study are; first, to investigate the dimensions of student decision quality and the structural relationships among them, and second, to investigate the influence of achievement goals on the dimensions. The study confirms that decision confidence, positive affect, and decision satisfaction are present-oriented, and attitudinal loyalty intention is future-oriented of decision quality. Mastery goals positively influence, and conversely, performance-approach goals and performance-avoidance goals negatively influence all of the student quality dimensions. Therefore, high mastery goals are the key to high attitudinal loyalty intention and low switching likelihood. On the other hand, a high performance-approach and performance-avoidance goals should be the early indications of a low attitudinal loyalty intention and high switching likelihood and vice versa. Future researchers can consider a longitudinal research design to detect the change in achievement goals and their impacts within a period. Keywords: Achievement goals, decision confidence, self-efficacy, expected outcomes, positive affection, loyalty intention. JEL Classifications: M31, D81, I21 DOI: https://doi.org/10.32479/irmm.10088